2022
DOI: 10.1007/jhep01(2022)179
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, symmetries, anomaly and vortices in a rotating cosmic string background

Abstract: Non-relativistic conformally invariant systems in a rotating cosmic string (conical) spacetime are analyzed at the classical and quantum levels by means of the gravitoelectromagnetic interpretation of the background. Solutions of the equations of motion are found by employing a local canonical transformation, that leads to their natural interpretation in terms of Riemann surfaces. The cone parameter α and the angular velocity Ω of the background determine the existence of hidden symmetries. Globally defined hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The present article aims to construct supersymmetric extensions of this model on the real line and of its generalization in the Euclidean plane. The resulting systems are interesting for their connection with the spin-1/2 Landau problem, the models in the presence of Aharonov-Bohm flux associated with anyons [52][53][54][55], the physics of Bose-Einstein condensates in rotating harmonic traps [56,57], and gravitoelectromagnetism [58].…”
Section: Jhep08(2022)228mentioning
confidence: 99%
See 2 more Smart Citations
“…The present article aims to construct supersymmetric extensions of this model on the real line and of its generalization in the Euclidean plane. The resulting systems are interesting for their connection with the spin-1/2 Landau problem, the models in the presence of Aharonov-Bohm flux associated with anyons [52][53][54][55], the physics of Bose-Einstein condensates in rotating harmonic traps [56,57], and gravitoelectromagnetism [58].…”
Section: Jhep08(2022)228mentioning
confidence: 99%
“…This mapping relates the symmetry generators and eigenstates of asymptotically free and harmonically confined versions of the so(2, 1) ∼ = sl(2, R) conformal mechanics models (e.g., of the free particle and the harmonic oscillator in the simplest case). In this way, we identified hidden symmetries and spectra of different harmonically trapped systems in a monopole [65] and cosmic string backgrounds [58,66], and constructed exotic rotational invariant harmonic oscillator (ERIHO) related to the physics of Bose-Einstein condensates [57] and gravitoelectromagnetism [58]. The CBT was also applied to the study of the black holes mechanics in ref.…”
Section: Jhep08(2022)228mentioning
confidence: 99%
See 1 more Smart Citation
“…Its compact form allowed analytical research studies of many physical and mathematical systems in gravitational backgrounds with rotation and causality violation. It has been shown that all spacetime homogeneous (ST-homogeneous) Gö del-type metrics characterized by the vorticity Ω of spacetime (a real number that is related to rotation of the material, i.e., | | W =  W [8]) and a given value of the parameter ˜m m -¥ ¥   ; 2 , can be transformed in cylindrical coordinates [8][9][10][11][12][13][14][15][16][17][18] to Here, the disclination parameter α (curvature parameter) admits the values 0 < α < 1 in general relativity (for cosmic strings with positive curvature), α > 1 in the geometric theory of defects in condensed matter (for a negative curvature), and Ω = 0 and α = 1 corresponds to Minkowski flat spacetime metric. Moreover, for m < 0 2 there is an infinite number of successive causal and noncausal regions, and for m < W  0 2 2 there is one noncausal region for a given r > r c .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the covariant and contravariant metric tensors associated with the Som-Raychaudhuri spacetime are, respectively, given by The objective of the current methodical proposal is to explore in a comprehensive manner the effect of the gravitational field generated by the Gödel-type cosmic string SR-spacetime equation (2) on the spectra of some Klein-Gordon (KG) particles of fundamental quantum gravity nature, like the KG-oscillators and KG-Coulomb models. Such fundamental models have been studied by different authors (e.g., [12][13][14][15][16][17][18][22][23][24]) where the vorticity parameter Ω is assumed to take the form Ω 0 and the energies are assumed to be positive…”
Section: Introductionmentioning
confidence: 99%